Live Single-Cell Metabolomics With Matrix-Free Laser/Desorption Ionization Mass Spectrometry to Address Microalgal Physiology - Baumeister, Tim U. H.; Vallet, Marine; Kaftan, Filip; Svatoš, Aleš; Pohnert, Georg (Frontiers in Plant Science, 2019)
Single cell heterogeneity of unicellular organisms within a population is generated by external cues or random genetic mutations. This causes a non-uniform phenotype within populations, with the potential to impact the response of the entire ecosystem. Here, we propose an effective, rapid and versatile method to analyze single cells associated to aqueous substrate with laser-desorption/ionization mass spectrometry (LDI-MS) using a simple and inexpensive matrix-free support. The cells deposited on a cultivation-medium wetted support are analyzed with minimal disturbance as they remain in their natural viable state until their disruption during LDI-MS. Metabolites desorbed from single cells are analyzed on High-Resolution Mass Spectrometry (HRMS) using the Orbitrap FT-MS technology to broadly fingerprint cellular chemistry. This single-cell mass spectrometry (SC-MS) allows assessing the physiological status and strain-specificity of different microalgae, including diatoms and chlorophytes, at the single-cell level. We further report a reliable and robust data treatment pipeline by performing multivariate statistics on the repeated SC-MS measurements. Comparing single cell MS spectra from natural phytoplankton samples and from laboratory strains allows the identification and discrimination of inter and intra-specific metabolic variability and thereby has promising applications in determining the taxonomic composition of highly complex phytoplankton blooms. Notably, the herein described matrix-free live-single-cell LDI-HRMS approach enable monitoring dynamics of the plankton and explain why key-players cells survive, thrive, avoid selective feeding or pathogenic virus and bacteria, while others are overcome and die.